Palestine in the Aftermath of the Arab Conquest: the Earliest Latin Account - O'Loughlin, Thomas (Studies in church history, 2000)
Written, probably, in the early 680s on lona, Adomnán’s De locis sanctis has excited interest, and been used as a quarry for facts about the Holy Land, ever since. It purports to report the pilgrim experiences of a ‘bishop of the Gaulish race’ (prooemium, I), Arculf, who, when later on Iona, told of what he had seen in Palestine, Alexandria, and Constantinople. Realising his ‘scoop’, Adomnán set the details down in a permanent record. Within twenty years this formed the basis of a more concise account by Bede, who added a few details of his own about Arculf which have become standard elements of the latter’s biography: the pilgrim, returning home, was blown by a gale on to the western shores of Britain, and thence he travelled to Iona where he told his story. However, while Arculf - through either Adomnán’s or Bede’s account - is the focus of attention in scholarship using these works as evidence, Bede recognized the expertise of Adomnán in the work, and did not reduce him to the status of an amanuensis.